Maraknya Kekerasan Pada Lingkungan Sekolah - Annisyah Ramadhani; Indri Eka Purnama (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Student delinquency cannot be separated from the impact in science that is constructed on the pattern of subject-object relationships. Through the objectivity of the education system in Indonesia, goals, principles, social organizations, teaching methods, assessments, students, curriculum, facilities and funding, this relational pattern is rooted. Violence against children is no longer limited to the private sector, but extends to wider society. Schools are places where violence occurs in children and this is a concern that is often discussed. Not only teachers can commit violence against students, but fellow students themselves can also commit violence against children. Bullying is the form of violence most often perpetrated by female students, and physical violence, such as fighting and threats, is most often perpetrated by female students. There are four times when children are most likely to experience violence. During recess, after school, when changing classes, and when no one is in class. Most violent incidents occur outside the school environment, not within the school environment. One way to prevent bullying at school is to explain the causes of the problem by considering the function and role of education at home, school and society.